Hydrological Response of Coniferous Forest in Temperate Region of Himachal Pradesh - Singh, R. P. (Indian Forester, 1989)
The role of forest in hydrological behaviour of a watershed is well recognised. The present paper deals with the different aspects of hydrological cycle in coniferous forests of Himachal Pradesh and some suggestions have been made to minimize the soil erosion and sedimentation.